2012
DOI: 10.1111/j.1467-9507.2012.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Going It Alone: Comparing Subtypes of Withdrawal on Indices of Adjustment and Maladjustment in Emerging Adulthood

Abstract: Scholars have distinguished conceptually between multiple forms of social withdrawal among children and adolescents, but this distinction has yet to be investigated fully during emerging adulthood. Therefore, the overarching goal of this study was to employ a person-oriented approach to examine differences between subtypes of withdrawal on indicators of internalizing issues and relationships in emerging adulthood. The sample for the current study (M age = 19.60, SD = 1.85, range = 18-29) consisted of 791 under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
201
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(222 citation statements)
references
References 27 publications
(46 reference statements)
20
201
1
Order By: Relevance
“…depression, anxiety and psychosomatic complaints) and psychiatric disorders (e.g. social phobia, avoidant personality disorder, and generalized anxiety disorder) [15][16][17]. Also, shy adolescents and early adults tend to show problems in expressing one's own opinions or talking in the presence of others, in meeting people, and establishing and maintaining relationships resulting in having fewer social relationships, which are less intimate and supportive [4,18].…”
Section: Shyness and Maladjustmentmentioning
confidence: 99%
“…depression, anxiety and psychosomatic complaints) and psychiatric disorders (e.g. social phobia, avoidant personality disorder, and generalized anxiety disorder) [15][16][17]. Also, shy adolescents and early adults tend to show problems in expressing one's own opinions or talking in the presence of others, in meeting people, and establishing and maintaining relationships resulting in having fewer social relationships, which are less intimate and supportive [4,18].…”
Section: Shyness and Maladjustmentmentioning
confidence: 99%
“…It was also found that shy children who had a best friend were perceived by the peer group as friendly and popular (Rubin et al, 2006). Nevertheless, previous studies have found that the quality of their friendships was inferior to that of children who are not shy (Lund, 2008;Nelson, 2013;Nelson et al, 2008).…”
Section: Educators' Positions With Regard To the Need To Help The Shymentioning
confidence: 84%
“…During the period of emerging adulthood, the individual must rely on himself and take responsibility for various tasks of daily life, both personal and professional, which require involvement in numerous social interaction. Consequently, shyness at this age presents a threat to emotional well-being (Nelson, 2013). It was found that shy people in their 20's experience high levels of depression and anxiety and perceive themselves in a (relatively) negative way; They also report a lower quality of relationships with friends and romantic partners (Nelson et al, 2008) and insecure romantic attachment beliefs (Rowsell & Coplan, 2013).…”
Section: Teacher's Understandings Regarding Shy Pupilsmentioning
confidence: 97%
See 1 more Smart Citation
“…Shy individuals, according to this model, want to interact but at the same time feel wary and anxious about interacting. Shyness first appears in early childhood, but while some children outgrow shyness, others seem to retain the feeling of shyness into young adulthood (Nelson, 2013).…”
Section: Introductionmentioning
confidence: 99%